Authenticity in Tourism Experiences: a new approach based on Edgar Morin’s Complexity Theory - Matos, Mariana Bueno de Andrade (2018)
This essay aims to provide an alternative lens for interpreting the construct ‘authenticity’ in the context of tourist experiences. The literature review presents the main authors of the field and its different known types of authenticity, among them the objective, constructivist and existential authenticity. The analysis and reflection of these different perspectives provide the basis for proposing the adoption of an alternative epistemological ground to the interpretation of authenticity in tourist experiences, which may lead to a better understanding of this phenomenon. Thus, it is proposed that Edgar Morin's Complexity Theory may offer a complementary view to the understanding of authenticity in the context of tourism, insofar as it may allow an alternative to the traditional fragmented way of thinking, and reflections from a more holistic view of the phenomenon. This discussion resulted in propositions, which are discussed at the end of this paper.